Structure of Intuitionistic Fuzzy Sets in Γ-Semihyperrings - Bayram Ali Ersoy; Bijan Davvaz (Abstract and Applied Analysis)
As we know, intuitionistic fuzzy sets are extensions of the standard fuzzy sets. Now, in this paper, the basic definitions and properties of intuitionistic fuzzy Γ-hyperideals of a Γ-semihyperring are introduced. A few examples are presented. In particular, some characterizations of Artinian and Noetherian Γ-semihyperring are given.